2020
DOI: 10.1063/5.0029596
|View full text |Cite
|
Sign up to set email alerts
|

Differential reflectivity spectroscopy on single patch nanoantennas

Abstract: We present an experimental technique adapted to characterize individual metallic nanostructure in terms of differential reflectivity spectroscopy. We analyze gold patch nanoantennas holding different morphological properties. Our experimental methodology shows steady and reliable results consistent with classical analytical approximations and simulation methods. This technique allows to identify absorption properties of metallic nanostructures commonly associated to surface plasmon resonances. By contrasting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Analyzing QD emission as a function of pump intensity, Zhang et al have reported a very similar trend [36]; here we observe higher nonlinearity and a larger absorption cross-section due to the antenna. Plasmonic interactions provide efficient ways of trapping and propagating light [37,38,39], which increases the effective absorption cross-section of these antennas [40,41]. Our measurements reveal a 1000-fold increase in the absorption cross-section due to the antenna.…”
Section: Antenna Emission Under Increasing Excitationmentioning
confidence: 80%
See 1 more Smart Citation
“…Analyzing QD emission as a function of pump intensity, Zhang et al have reported a very similar trend [36]; here we observe higher nonlinearity and a larger absorption cross-section due to the antenna. Plasmonic interactions provide efficient ways of trapping and propagating light [37,38,39], which increases the effective absorption cross-section of these antennas [40,41]. Our measurements reveal a 1000-fold increase in the absorption cross-section due to the antenna.…”
Section: Antenna Emission Under Increasing Excitationmentioning
confidence: 80%
“…Analyzing QD emission as a function of pump intensity, Zhang et al have reported a very similar trend; [36] here we observe higher nonlinearity and a larger absorption cross-section to the antenna. Plasmonic interactions provide efficient ways of trapping and propagating light, [37][38][39] which increases the effective absorption cross-section of these antennas. [40,41,46,47] Our measurement shows that in comparison to the absorption cross-section of a typical QD (see the Supporting Information), the absorption cross-section of the presented QD+antenna system is 1000 times more, or in other words, the presented antenna induces a 1000-fold effective increase in the emitter absorption cross-section.…”
Section: Antenna Emission Under Increasing Excitationmentioning
confidence: 99%